Русско-словенские лексические параллели - Коницкая, Елена Михайловна Михайловна (Slavistica Vilnensis, 2011)
Jelena Konickaja Russian-Slovene Lexical Parallels The article examines word pairs in two Slavic languages, Russian and Slovene, that stem from a shared etymon, or root in the shared protolanguage. These words can preserve a certain similarity on both the phonological (expressive) and semantic (content) levels. Within the analysis such doublets can also be included other pairs that relate to a given lexicosemantic field: for example, Rus. tverdyj – Slov. trd, trden; Rus. krepkij, cherstvyj – Slov. krepak, čvrst. The article proposes using minimal-context translation, avoiding word formations and sentences, in order to establish differential semes, or semantic components. A set of differential semes is presented for Rus. celyj, ves’ – Slov. cel, ves.